2013
DOI: 10.1242/dev.090902
|View full text |Cite
|
Sign up to set email alerts
|

Dual role for Hox genes and Hox co-factors in conferring leg motoneuron survival and identity in Drosophila

Abstract: SUMMARYAdult Drosophila walk using six multi-jointed legs, each controlled by ~50 leg motoneurons (MNs). Although MNs have stereotyped morphologies, little is known about how they are specified. Here, we describe the function of Hox genes and homothorax (hth), which encodes a Hox co-factor, in Drosophila leg MN development. Removing either Hox or Hth function from a single neuroblast (NB) lineage results in MN apoptosis. A single Hox gene, Antennapedia (Antp), is primarily responsible for MN survival in all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 51 publications
5
76
0
Order By: Relevance
“…To characterize the lineages that give rise to the adult thoracic NG, we carried out several clonal analysis experiments. Previous observations demonstrated that NB lineages such as Lin A (also called Lin 15), produce both leg motor neurons and glial cells (Baek et al, 2013; Truman et al, 2004). This observation raised the intriguing possibility that NG and leg motor neurons may share common developmental origins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the lineages that give rise to the adult thoracic NG, we carried out several clonal analysis experiments. Previous observations demonstrated that NB lineages such as Lin A (also called Lin 15), produce both leg motor neurons and glial cells (Baek et al, 2013; Truman et al, 2004). This observation raised the intriguing possibility that NG and leg motor neurons may share common developmental origins.…”
Section: Resultsmentioning
confidence: 99%
“…Although each motor neuron morphology is thought to be determined by unique combinations of morphology transcription factors (mTFs; Enriquez et al, 2015), how these stereotyped morphologies form the correct synaptic connections with interneurons and sensory neurons is not understood. Interestingly, at least one of the major NB lineages that give rise to adult motor neurons in the fly also generates another important cell type in the nervous system, glia (Baek et al, 2013; Lacin and Truman, 2016), which are critical for the establishment of synapses and the maintenance of neuronal activity (Freeman, 2015; Freeman and Rowitch, 2013). The observation that glia and leg motor neurons may be derived from common progenitors (neuroglioblast [NGB]) raised the possibility that their development may be coordinated, and that being born from the same lineages might also play a role in neural circuit assembly.…”
Section: Introductionmentioning
confidence: 99%
“…This process may have been facilitated by partial duplication of cervical segments of the spinal cord (Hirasawa and Kuratani, 2013), which may have served to allow a new MN population to utilize Hox5 function in PMC specification, while preserving their function in LMC subtype specification. A similar strategy of co-option appears to have occurred during the development of insect nervous systems, as Hox genes have recently been shown to be instrumental in the development of peptidergic interneurons and leg-innervating motor neurons in Drosophila (Baek et al, 2013; Karlsson et al., 2010). …”
Section: Evolutionary Diversification Of Effector Neurons In Motor Symentioning
confidence: 94%
“…Recent studies using genetic manipulations in mouse and Drosophila have indeed shown that inhibition of apoptosis prevents regression of aberrant axonal projections in several neural systems, indicating a role for PCD in eliminating neurons that project to aberrant sites ( Figure 4G) (Baek et al, 2013;Buss et al, 2006;Jiang and Reichert, 2012;Rogulja-Ortmann et al, 2007).…”
Section: Neurons Targeting To ''Inappropriate'' Regionsmentioning
confidence: 98%
“…This is the case for a number of gene mutations that lead to the mis-targeting of neural projections. For instance, flies harboring mutations in homeobox genes that determine neuronal identity, such as Antp, labial, Dfd, and Scr, exhibit aberrant axonal targeting and such aberrant neurons are eliminated by PCD in those mutants (Baek et al, 2013;Kuert et al, 2012Kuert et al, , 2014. Thus, mechanisms that couple the control of neuronal identity with projection patterning might underlie regulatory processes that lead to the elimination of aberrant neurons by PCD.…”
Section: Neurons Targeting To ''Inappropriate'' Regionsmentioning
confidence: 99%